Neopatrimonialism Revisited - Beyond a Catch-All Concept - Gero Erdmann; Ulf Engel (German Institute of Global and Area Studies (GIGA), 2006)
The article provides a critical discussion of the literature on 'patrimonialism' and 'neopatrimonialism' as far as the use in Development Studies in general or African Studies in particular is concerned. To overcome the catch-all use of the concept the authors present their own definition of neopatrimonialism based on Max Weber's concept of patrimonialism and legal-rational bureaucracy. However, in order to make the concept more useful for comparative empirical research, they argue, it needs a thorough operationalisation (qualitatively and quantitatively) and the creation of possible subtypes which, in combination, might contribute to a theory of neopatrimonial action. – – Der Artikel unterzieht die beiden Konzepte 'Patrimonialismus' und 'Neopatrimonialismus', wie sie in der entwicklungstheoretischen Literatur und in Afrikastudien Verwendung finden, einer kritischen Analyse. Damit dem Konzept des Neopatrimonialismus mehr als nur eine heuristische Bedeutung zukommen kann, präsentieren die Autoren eine eigene Definition des Begriffs, die sich eng an die Weber'schen Konzepte des Patrimonialismus und der legal-rationalen Bürokratie anlehnt. Darüber hinaus ist auf dieser Grundlage (1) eine sorgfältige (qualitative und/oder quantitative) Operationalisierung des Konzeptes und (2) die Bildung von möglichen Subtypen notwendig. Erst dann kann das Konzept sinnvoll für die vergleichende empirische Forschung eingesetzt und möglicherweise etwas wie eine neopatrimoniale Handlungstheorie entwickelt werden.
Keywords: 300; neopatrimonialism; patrimonial and legal-rational bureaucratic domination; hybrid regimes; rent seeking; Politisches System; Führungsstil; Bürokratie; Politische Entscheidung; Afrika